Maintenance in dental implants - Giselle Póvoa Gomes; Ronaldo Mendes Assis Lucena; Patrícia Barcelos Bastos; José Bernardes das Neves (Faculdade São Leopoldo Mandic, 2008)
In implants, maintenance is a decisive factor for obtaining success when implant supported overdentures and dentures are used. The present stud presents, a clinical case of a patient, a 70 year-old white man, with a completely edentulous mandibular alveolar ridge, severe bone resorption with presence of basal bone only, and absence of vestibule. Initially, treatment consisted of the placement of a mandibular overdenture, supported on three implants in the anterior inter-foramen region, as the left implant was transfixed in the basal bone of 2 to 3 millimeters. Eleven years later, another two implants were placed in the anterior area and an immediate load was performed up to the first molars, for the placement of an implant supported fixed. Throughout the entire treatment, meticulous maintenance was carried out, with follow-up for fourteen years, interrupted by the patient's death. From the third month after the opening the three implants initially placed, the presence of keratinized mucosa, definition of the vestibule, maturation of the alveolar ridge and bone formation in the mento region were observed. It was concluded that good planning, allied to mastery of the technique and adequate maintenance were the prerequisites necessary for obtaining favorable results, success of the present case, and for the patient to have a better quality of life.